LEADERSHIP OF MADRASAH HEADS IN IMPROVING THE QUALITY OF ADMINITRATION PERFORMANCE - Muhamad Khoirul Umam (Universitas Muhammadiyah Ponorogo, 2020)
This research is based on a phenomenon in relation to the leadership of the head of Madrasah in Islamic education institutions which is a formal Islamic boarding school based madrasah that contrasts with the embodiment of Islamic education institutions. In order to carry out its role as a leader, the headmaster must have the right strategy to improve the quality of his administrative staff through cooperation or cooperation, giving the administrative staff the opportunity to improve their profession and encourage the involvement of all administrative personnel in various activities that support the madrasah program. The focus of this study are:1. How is the Policy of the Head of Madrasah in Improving the Quality of Performance of Administrative Staff? 2. How is the Motivation of Madrasah Heads in Improving the Quality of Administrative Staff Performance? 3. How to inhibit the Head of Madrasah in Improving the Quality of Administrative Staff overcome it? This type of research is a field research with a phenomenological approach, a qualitative descriptive research method, so that the approach taken is a qualitative approach using a case study design, data analysis with an inductive approach. From the results of this study, the authors conclude that: 1) The Policy of the Head of Madrasah in Improving the Quality of Performance of Administrative Personnel is in the formation of character in the form of discipline and exemplary that is by processing the awareness of the whole Madrasa citizens. 2) Motivation of Head of Madrasah in Improving the Quality of Performance of Administrative Personnel in the attitude that is always responsive from the Head of Madrasah to the subordinates by giving encouragement, guidance, direction, training, and appreciation for work performance. 3) Inhibiting Factors of Madrasah Heads in Improving the Quality of Administrative Staff Performance and how to overcome them are in discipline and orderliness in work. In overcoming Madrasah heads by enforcing exemplary attitudes for all Madrasah citizens.